(3GdOQ GdefKhQ aj GdYed HQHY GdOSJhQs - (3CHh YHO GdQMef LeGd GdOjf YHO Gddg Hf Ndjd Hf jhSa GdeGQOjfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY GdSeGhGJ HZjQ YeO hHYO , abO SCdfi HYV ENhGfi GdUGdMjf , ef Cgd GdYde GdMPGb , Cf CLeY dg TjFkG ai Yde GdehGbjJ dSGFQ GdBaGb hLeYJ gPg GdQSGdI hSejJgG HGdOQ GdefKhQ ai GdYed HQHY GdOSJhQ s
(3BNQgG (B:s
(3hcPdc cd eSCdI JQLY Edi GdCYOGO GdefGSHI ef ZjQ EMJjGL Edi eG PcQg GdeJbOehf ef JfRjd GdeSGFd ai gPg GdBdI , hCSGd Gddg GfJgi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B93 - (3U(B129s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B270s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B218 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B_ (3GdQHGW (B(221(3O(B) s
Keywords: (3Gdadcs